Contribution the Failure Mode Analysis and Criticality Evaluation Method to the Rehabilitation of Cork Oak (Quercus suber) Forests in Forest Massif of Tlemcen (Algeria) - Aman Bouzid; Khadidja Bouzid; Kheloufi Benabdeli (Jurnal Manajemen Hutan Tropika, 2022)
The controling of forest sustainability and preforest ecosystems in achieving stability of forest ecosystem require the identification of biophysical indicators, anthropological, and technological. The significant degradation of Quercus suber formations in forest massif of Tlemcen (Algeria) are imposed by both climatic factors, the fires, the overgrazing land, anthropogenic aggression as well as by ineffective management. The making of a reference matrix would make possibility the identification of probable hazards and risks. This study aimed to identify the understanding how the mode of operation of a system to identify failures and treat, and the create the intention of eliminating or minimizing the associated risks. This matrix will consist of relevant indicators which easy guide to estimate and following the understanding of the forest degradation process in Algeria. The FMECA method allowed identification of 20 main defective targets which be grouped into 3 categories namely: technical, ecological, organizational, and facilitate of remediation. Each error can be scored and action plans can be prioritized, allowing different with all forest sector players to better understand the degradation of this natural space in order to implement efficient and appropriate remediation plans.